Preconception management of women with obesity: A systematic review. (13th December 2018) - Price, Sarah A.; Sumithran, Priya; Nankervis, Alison; Permezel, Michael; Proietto, Joseph
Summary: The prevalence of women of child‐bearing age with obesity continues to rise at an alarming rate. This has significant implications for both the short‐term and long‐term health of mother and offspring. Given the paucity of evidence‐based literature in this field, the preconception management of women with obesity is highly variable both between institutions and around the world. This systematic review aims to evaluate studies that inform us about the role of preconception weight loss in the fertility and pregnancy outcomes of women with obesity. Current therapeutic interventions are discussed, with a specific focus on the suitability of weight loss interventions for women with obesity planning pregnancy. There are significant knowledge gaps in the current literature; these are discussed and areas for future research are explored.